1990
DOI: 10.1002/ar.1092260409
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of laminin in the murine pituitary

Abstract: The distribution and cellular localization of the glycoprotein laminin were investigated by light and electron microscopic immunocytochemistry in the adult murine pituitary gland. Immunoblots confirmed that laminin was the only protein in the pituitary gland of the adult male mouse to react with antilaminin serum. Laminin immunoreactivity was demonstrated at the light microscopic level simultaneously with that of beta-follicle stimulating hormone (beta-FSH) and beta-luteinizing hormone (beta-LH). In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In contrast to other tissues, the specific laminin isoforms expressed in the anterior pituitary have not been identified, although several studies have confirmed the presence of laminin protein in this gland [10, 11, 13, 19]. In the present study, we used RT-PCR to identify laminin chains expressed in the anterior pituitary.…”
Section: Introductionmentioning
confidence: 84%
“…In contrast to other tissues, the specific laminin isoforms expressed in the anterior pituitary have not been identified, although several studies have confirmed the presence of laminin protein in this gland [10, 11, 13, 19]. In the present study, we used RT-PCR to identify laminin chains expressed in the anterior pituitary.…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, within these cells, laminin immunoreactivity was found only in secretory granules and not in Golgi cisternae nor in the endoplasmic reticulum or nuclear envelope. Laminin was not found in the extracellular connective tissue [86].…”
Section: Gonadotrophsmentioning
confidence: 79%
“…Laminin is also a constituent of the basal laminae in the adenohypophysis of the mouse pituitary gland [86]. Moreover, within these cells, laminin immunoreactivity was found only in secretory granules and not in Golgi cisternae nor in the endoplasmic reticulum or nuclear envelope.…”
Section: Gonadotrophsmentioning
confidence: 95%
“…In addition, immunocytochemical studies have demonstrated the presence of laminin in the secretory granules of rat anterior pituitary (15)(16)(17) and in gonadotrophs in mouse pituitary (18). In these reports, the absence of laminin A chain in the granules was demonstrated by immunoblotting (17,18). The role of laminin in these secretory granules is unknown at present.…”
mentioning
confidence: 99%